2008
DOI: 10.5432/ijshs.ijshs20080314
|View full text |Cite
|
Sign up to set email alerts
|

Development and Gender Differences in Dynamic and Kinetic Visual Acuities in Children from 8 to 17 Years of Age

Abstract: This study was conducted to elucidate the development and gender differences in dynamic and kinetic visual acuities in children from 8 to 17 years of age. The subjects were 867 boys and girls. The test parameters were static visual acuity, kinetic visual acuity, and dynamic visual acuity and the test was done using a method that allowed evaluation of many subjects in a short time. The speed at which the target moved started at 40 rpm and was reduced gradually thereafter in measurement of dynamic visual acuity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Contrast sensitivity is ability to distinguish between dark and light. Contrast sensitivity was measured using a Sine Wave Contrast Test (Stereo Optical Co., Inc., Chicago, IL, USA) (Kohmura et al, 2008; Furuta et al, 2009), and contrast sensitivity was measured at each spatial frequency of 1.5, 3, 6, 12, and 18 cycles/degree. Each of the circles in the cart contains lines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrast sensitivity is ability to distinguish between dark and light. Contrast sensitivity was measured using a Sine Wave Contrast Test (Stereo Optical Co., Inc., Chicago, IL, USA) (Kohmura et al, 2008; Furuta et al, 2009), and contrast sensitivity was measured at each spatial frequency of 1.5, 3, 6, 12, and 18 cycles/degree. Each of the circles in the cart contains lines.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic visual acuity was measured using a dynamic visual acuity test apparatus (HI-10, Kowa Co., Ltd., Aichi, Japan) (Kohmura et al, 2008). In this test, the subject attempted to determine the direction of the gap in a Landolt ring moving from left to right on a semi-circular screen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…KVA was not improved by either training although some effects on visual function were observed 21) . A subsequent study with junior high school students also revealed that training did not improve KVA 22) .…”
Section: Factors Associated With Kvamentioning
confidence: 93%
“…Kohmura et al studied 867 men and women aged 8-17 years and reported that DVA developed gradually with age, but KVA did not change from age 8 to 17 years 23) . Therefore, KVA is expected to reach almost the same level as adults by the age of 8 years 23) .…”
Section: Factors Associated With Kvamentioning
confidence: 99%